2017
DOI: 10.1186/s13100-017-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic silencing of somatic L1 retrotransposon insertions reflects the developmental and cellular contexts of their genomic integration

Abstract: BackgroundThe ongoing mobilization of mammalian transposable elements (TEs) contributes to natural genetic variation. To survey the epigenetic control and expression of reporter genes inserted by L1 retrotransposition in diverse cellular and genomic contexts, we engineered highly sensitive, real-time L1 retrotransposon reporter constructs.ResultsHere we describe different patterns of expression and epigenetic controls of newly inserted sequences retrotransposed by L1 in various somatic cells and tissues includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
(114 reference statements)
3
12
0
Order By: Relevance
“…Interestingly, I found that de novo L1 remained quite hypomethylated during neural induction and neurodifferentiation. This result is consistent with previous publications that found sustained hypomethylation of de novo full-length L1 insertions from an engineered L1 reporter [222]. Therefore, I speculate that host genomes may need some rounds of cell cycling to recognize a de novo retrotransposition event and activate their defence mechanisms, in this case at the epigenetic level.…”
Section: Chapter 4: Discussionsupporting
confidence: 93%
“…Interestingly, I found that de novo L1 remained quite hypomethylated during neural induction and neurodifferentiation. This result is consistent with previous publications that found sustained hypomethylation of de novo full-length L1 insertions from an engineered L1 reporter [222]. Therefore, I speculate that host genomes may need some rounds of cell cycling to recognize a de novo retrotransposition event and activate their defence mechanisms, in this case at the epigenetic level.…”
Section: Chapter 4: Discussionsupporting
confidence: 93%
“…In general, the evaluation of L1–RTP through reporter gene expression causes an underestimation of L1 retrotransposition events, because the reporter cassettes integrated in epigenetically silent insertional site cannot be detected (Garcia‐Perez et al ., ; Kannan et al ., ; Macia et al ., ) and multiple retrotransposition events in a single transfected cell cannot be discriminated as well (Wei et al ., ). To gain further information, evaluation of the number of inserted engineered L1, regardless of their expression, can be carried out by quantitative real‐time PCR assays, in addition to the measurement of the reporter gene expression (Del Re et al ., ).…”
Section: Methodological Approachesmentioning
confidence: 98%
“…As the retrotransposition capacity of a donor L1 depends on its epigenetic regulation in a particular cell, in addition to the enzymatic efficiency of its encoded proteins, it will be interesting to determine whether de novo daughter insertions in vivo are subjected to the same epigenetic and host factor regulation as pre‐existing genomic elements, or whether there is some delay in establishing epigenetic marks upon newly‐integrated L1 copies. Recent studies employing engineered L1 elements in mouse embryonic stem cells and transgenic mice suggest the former scenario is more likely …”
Section: Heritable L1 Retrotransposition Is An Ongoing Processmentioning
confidence: 99%